ANALISIS PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, SOLVABILITAS DAN ARUS KAS TERHADAP OPINI AUDIT (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Tomi Riyadi (Prima Center Indonesia, 2019)
The purpose of this research is to provide empirical evident about profitability, liquidity, solavability and cash flow that effect probability of opinion audit. The financial ratios which researched those are Return on Assets Ratio, Return on Equity Ratio, Current Assets Ratio, Quick Asset Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Cash Flow to Asset Ratio and Cash Flow to Sales Ratio as independent variables and Audit Opinion as dependent variable. The samples consist of 200 samples whereas observed period from 2010 to 2014 on manufactured industries which listed in Indonesia Stock Exchange. Moreover, it chooses by purposive sampling whereas it is based on some criterias. The statistic method used to test on the research hypothesis is multinomial logit regression. The result of this research shows that Return on Asset Ratio, Quick Asset Ratio and Debt to Asset Ratio are significant variables in prediction the probability the company will get unqualified opinion. This research also indicate that Debt to Asset Ratio is significat variable in prediction the probability hte company will get qualified opinion.Keywords: Financial ratios, Profitability ratio, Liquidity ratio, Solvability ratio, Cash Flow ratio, Audit Opinion and Multinomial Logit Regression